THE EFFECTS OF PRENATAL COCAINE EXPOSURE ON EXECUTIVE FUNCTIONING IN ADOLESCENTS - Daniels, Laura M. (East Carolina University, 2011)
Executive functioning refers to higher-order cognitive skills (e.g., inhibition, shifting and sequencing), which improve with frontal lobe maturation from childhood through early adulthood. Research on executive functioning in children with prenatal cocaine exposure (PCE) has yielded inconsistent results, with some studies showing poorer performance for children with PCE compared to typically developing controls and others showing no group differences. To date the literature on the effects of PCE on executive functioning has been limited to early and middle childhood. The frontal lobe and associated brain regions involved in executive functioning undergo extensive development during late childhood and adolescence. Questions remain about whether subtle negative effects of PCE become more evident with specialization of the brain regions involved in executive functioning. The purpose of the current study was to assess the effects of PCE on executive functioning measures in adolescence. Participants (N = 50, 14 - 16 years) are predominantly African American living in rural communities and of lower socio-economic status and at birth were prospectively enrolled in a longitudinal study. Adolescent participants were administered four measures of executive functioning abilities of increasing complexity: the Stroop Color-Word Test (Stroop), Trail Making Test (TMT), Wisconsin Card Sorting Test (WCST), and Iowa Gambling Task (IGT). Group comparisons between PCE and non-PCE adolescents were made using the Wilcoxon Rank Sum test and the ANOVA was used to determine whether there was a PCE by gender interaction. Multiple regression modeling was used to assess the unique effect of PCE on executive functioning performance while controlling for other drug exposures and gender. Results indicated that there were no group differences between PCE and non-exposed adolescents and no evidence of a PCE by gender interaction on any of the measures of executive functioning. None of the models for predicting Stroop, TMT, WCST, or IGT scores were statistically significant. In this sample of adolescents, there was no evidence indicating that PCE predicts outcomes of executive functioning performance. This study adds to a growing literature base demonstrating that PCE is not related to significant decrements in executive functioning when compared to a well-matched control group.
Keywords: Psychology; Adolescents; Cocaine; Executive functioning; Prenatal cocaine exposure; Children of prenatal substance abuse--Development; Cognitive psychology; Prenatal influences; Cocaine abuse; Inhibition in children